Translation and validation of Hindi version of Oral Health Impact Profile-14 - Neeraj Chandrahas Deshpande; Abhay Avinash Nawathe (Wolters Kluwer Medknow Publications, 2015)
Title of the Study: Validation of Hindi Version of Oral health Impact Profile (OHIP-14) Aim: To validate the Hindi version of OHIP-14. Settings and Design: The study was carried out in K.M. Shah Dental College & Hospital, Vadodara. Materials and Methods: OHIP-14 was translated into Hindi language.102 participants were given English as well as Hindi versions of OHIP-14. Statistical Analysis Used: Individual question were analyzed using Pearson Chi-Square test, Likelihood Ratio test and Linear-by-Linear Association test. The entire questionnaire in English and Hindi language were comparatively analyzed using Unpaired T test & Pearson correlation coefficient test. Results: All the 14 questions showed no statistically significant difference between the English OHIP-14 and the translated Hindi version of OHIP-14. Results of Unpaired T test (P = 0.61) were statistically insignificant. Pearson Correlation coefficient test was 0.963 suggesting that the translated Hindi version was highly correlated to the original English version. Conclusion: The translated Hindi version of OHIP-14 is hence established as a valid tool for conduction of oral health related & quality of life surveys in Hindi language which is the most commonly used language in the Indian subcontinent.